NILAI-NILAI KARAKTER RITUAL KING HO PING SEBAGAI SUMBER BELAJAR IPS (Harmony: Jurnal Pembelajaran IPS dan PKN, 2020)
The purpose of this research is to find out the King Ho Ping ritual procession and character values ​​in the King Ho Ping ritual as a source of social studies learning. This research uses a qualitative approach with a phenomenological research design. This research is located in the Hok Swie Bio temple in Bojonegoro Regency. The results showed that the King Ho Ping ritual began with a shadow puppet show continued with musical performances and Liong and Barongsai attractions. The climax of the ritual is to pray three times and the end of the ringing signal as a sign of the procession of the gunungan battle begins. Sub character values ​​that arise are 1) respecting differences in religion and belief; 2) firm stand; 3) cooperation between followers of religion; 4) appreciation of the nation's own culture 5) maintain the nation's cultural richness; 5) respect for diversity, ethnicity, religion and culture; 6) please help; 7) anti-discrimination; 8) lifelong pursuit; and 9) responsibilities. Marketer values ​​in the King Ho Ping ritual can be integrated in social studies learning materials in a thematic integrated social studies learning design based on topics, namely the integration of social life with the integration of geography, history, sociology, and economics. Tujuan dalam penelitian ini yaitu untuk mengetahui prosesi ritual King Ho Ping dan nilai-nilai karakter dalam ritual King Ho Ping sebagai sumber belajar IPS. Penelitian ini menggunakan pendekatan kualitatif dengan desain penelitian fenomenologi. Penelitian ini berlokasi di kelenteng Hok Swie Bio Kabupaten Bojonegoro. Hasil penelitian menunjukkan bahwa ritual King Ho Ping dimulai dengan acara pergelaran wayang kulit dilanjutkan dengan karawitan dan atraksi Liong serta Barongsai. Puncak ritual dilakukan sembahyang sebanyak tiga kali putaran dan diakhir bunyi gendering sebagai tanda prosesi rebutan gunungan dimulai. Sub nilai-nilai karakter yang muncul yaitu 1) menghargai perbedaan agama dan kepercayaan; 2) teguh pendirian; 3) kerja sama antar pemeluk agama; 4) apresiasi budaya bangsa sendiri 5) menjaga kekayaan budaya bangsa; 5) menghormati keragaman, suku, agama dan budaya; 6) tolong menolong; 7) anti diskriminasi; 8) pembejaran sepanjang hayat; dan 9) tanggung jawab. Nilai-nilai karketer dalam ritual King Ho Ping dapat diintegrasikan dalam materi pembelajaran IPS dalam desain pembelajaran IPS terpadu tematik berdasarkan topik yaitu integrasi kehidupan sosial dengan keterpaduan geografi, sejarah, sosiologi, dan ekonomi.